High precision U-series dating of scleractinian cold-water corals using an automated chromatographic U and Th extraction - Wefing, Anne-Marie; Arps, Jennifer; Blaser, Patrick; Frank, Norbert (Chemical geology, 2017)
High-precision U-series dating of scleractinian cold-water corals is a key chronological tool for studies of past environmental and climate conditions. Here, we tested and optimized an automated chemical extraction system (ESI prepFAST-MC equipped with an Eichrom TRU-resin chromatographic column) for its ability to purify U and Th isotopes for mass spectrometric U-series dating at the sub-‰ precision level. Chemical yields are constantly high, on average around 90% for both U and Th. Analytical blanks are comparable to manual purification (<0.15pg U, 0.15pg Th for a typical sample of 50mg) and memory effects due to the recycling of the column are mostly insignificant as the carry-over fraction is about 10−5 for Th and 10−3 for U isotopes. However, it was found that the built-in UTh (TRU-resin) column must be pre-conditioned for analysis using >1μgg−1 Th and U in order to achieve the above mentioned chemical yields. This conditioning has no impact on the Th/U data. The automated chemical preparation protocol described here is compared to conventional high precision U-series dating with manual sample purification. For the 34 cold-water corals extracted from a sediment core collected from a coral mound off Angola, the differences between 230Th/238U- and 234U/238U-ratios and U-series ages measured with the two analytical methods are smaller than the respective analytical uncertainty of <3.0‰, 0.8‰ and 3.0‰, respectively. Overall, ages of the studied corals span 34,000years and perfectly meet quality control constrains, such as initial seawater δ234U0. Finally, our record of coral ages indicates vigorous coral growth under warm and cold climate conditions in the temperate south-eastern Atlantic, contrasting climate influenced coral occurrences in the north-eastern Atlantic.